EVALUATION OF DIFFERENT DRYING METHODS FOR ORNAMENTALS BASED ON ACCEPTABILITY AND STORAGE OF DRIED PLANT PRODUCTS - JHANJI, SHALINI; PARMINDER SINGH,; K. K. DHATT,; H. S. GREWAL, (The Bioscan, 2018)
Dried ornamental products have novelty, longevity, flexibility and year round availability. The present study was conducted to standardize the drying methods for ornamental plants viz. flowers of Gomphrena, panicles of Golden Rod and peduncles of Golden Rain Tree. The plant parts were subjected to vertical, inverted and water drying and it was found that inverted drying took least time (4-5 days) for drying and least moisture retention after drying . The flowers of Gomphrena dried by inverted drying scored 10,10 and 8.89 respectively, for colour, shape and texture retention whereas the corresponding values were 8.44, 7.67 and 7.22, respectively for Golden Rod and 10, 9.11 and 7.22, respectively for Golden Rain Tree. The overall acceptability of all three ornamentals based on these parameters was found to be the best for inverted drying. The dried plant parts could be stored for more than 6 months with high acceptability score of 8.80, 7.40 and 8.67 respectively for Gomphrena, Golden Rod and Golden Rain Tree . Thus, the flowers of Gomphrena/ panicles of Golden rod/ peduncles of Golden Rain Tree can be dried best by hanging in inverted position in well ventilated dark room for 4-5days and can be used upto 6 months.